Ceramic Industry Wastewater Treatment by Chemical Coagulation Process - Pujiastuti, Caecilia; Egita Yulisningtyas; Ira Pareira (2477 - 6165, 2021)
Ceramic industrial waste contains organic compounds and several heavy metals that exceed the quality standards of ceramic industrial wastewater, therefore the wastewater is treated using the coagulation method. This study uses a coagulant Poly Aluminium Chloride (PAC) with the aim to determine the effect of coagulant mass and stirring time on reducing the content of COD, TSS, lead metal (Pb), and colour. Starting with the waste mixed with PAC has been diluted with a concentration of 1%. Then stirred using a flocculator with a speed of 100 rpm and time (2, 4, 6, 8, and 10 minutes) to form floc. Then it is deposited and separated between the filtrate and the solids. Then the filtrate was analysed. With this analysis, it can be seen that the highest reduction efficiency of TSS levels was 99.9% with a coagulant volume of 12.5 ml at 6 minutes. The highest efficiency of COD levels was obtained at 98.23% with a coagulant volume of 15 ml at 6 minutes. The highest efficiency of waste colour reduction was 99.85% with a coagulant volume of 15 ml at 10 minutes and the efficiency of reducing Pb levels was 99.10% with a coagulant volume of 5ml at 2 minutes, all of which were below the quality standard ceramic industry.